National Service : The Best Years of Their Lives - Royle, Trevor; Foreword by Peel, John (London Andre Deutsch, 2008)
More than 2 million men were conscripted to serve in Britain's armed forces during the period of National Service, which began after the Second World War and was phased out by 1963. Aged just eighteen, these individuals, were put in uniform to serve their nation. This work gives an account of the National Service years
Include Illustration, Notes and Index
Keywords: National service -- Great Britain -- Great Britain. Ministry of Labour and National Service